PENGARUH PELATIHAN EFIKASI DIRI UNTUK MENURUNKAN KECEMASAN MENGHADAPI UJIAN CBT PADA PESERTA UKMPPD - Dewi Lutfianawati; Vira Sandayanti; Supriyati Supriyati; Adelia Sucita (JURNAL PSIKOLOGI MALAHAYATI, 2022)
ABSTRACT : THE EFFECT OF SELF EFFICACY TRAINING TO REDUCE CBT EXAM ANXIETY ON UKMPPD EXAMINATION PARTICIPANTS  Anxiety in facing the UKMPPD exam can be one of the causes that affect performance and have an impact on graduation. One of the successes of students in exams is supported by good psychological conditions, namely students have good self-efficacy. Providing self-efficacy training can help improve the self-efficacy of students who will face the UKMPPD exam. This study aims to determine the effect of self-efficacy training on anxiety facing the CBT exam in UKMPPD participants, Faculty of Medicine, Malahayati University. This research is a quasi-experimental research with pre post control group design research which was conducted on 50 participants of UKMPPD crackers, Malahayati University, Bandar Lampung. Experiments were carried out by providing self-efficacy training to the experimental group to reduce anxiety. Data were analyzed using the Mann Whitney test. The results showed that there was a decrease in the level of anxiety in facing the UKMPPD exam between students who received self-efficacy training and those who did not receive self-efficacy training. So it is necessary to have a self-efficacy training program on a regular basis for participants who will take part in UKMPPD at Malahayati University. Keywords:  Anxiety, Self Eficacy, UKMPPD Kecemasan dalam menghadapi ujian UKMPPD dapat menjadi salah satu penyebab yang mempengaruhi performa dan berdampak pada kelulusan. Keberhasilan mahasiswa dalam ujian salah satunya didukung oleh kondisi psikis yang baik yaitu mahasiswa memiliki self efficacy yang baik. Pemberian pelatihan self efficacy dapat membantu meningkatkan self efficacy yang dimiliki mahasiswa yang akan menghadapi ujian UKMPPD. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan self efficacy terhadap kecemasan menghadapi ujian CBT pada peserta UKMPPD Fakultas Kedokteran Universitas Malahayati. Penelitian ini merupakan penelitian quasi eksperimen dengan desain penelitian pre post control group design yang dilakukan kepada 50 peserta retaker UKMPPD Universitas Malahayati Bandar Lampung. Eksperimen yang dilakukan dengan memberikan pelatihan self efficacy kepada kelompok eksperimen untuk menurunkan kecemasan. Data dianalisis menggunakan uji Mann Whitney. Hasil penelitian menunjukkan bahwa terdapat penurunan tingkat kecemasan dalam menghadapi ujian UKMPPD antara mahasiswa yang mendapatkan pelatihan self efficacy dan yang tidak mendapatkan pelatihan self efficacy. Sehingga perlu adanya program pelatihan self efficacy secara berkala pada peserta yang akan mengikuti UKMPPD di Universitas Malahayati. Kata Kunci : Kecemasan, Self Efficacy, UKMPPD